Experimental Study on Solar Heat Battery using Phase Change Materials for Parabolic Dish Collectors - Ramalingam Senthil; Inbaraj Infanta Mary Priya; Mukund Gupta; Chinmaya Rath; Nilanshu Ghosh (International Journal of Renewable Energy Development, 2021)
Energy consumption has increased withthe population increase, and fossil fuel dependency has risen and causing pollutions. Solar energy is suitableto provide society's thermo-electric needs. Thermal energy storage-based concentrated solar receivers are aimed at store heat energy and transportable to the applications. Acavity receiver with two-phase change materials (PCM) is experimentally investigated using a parabolic dish collector to act as the solar heat battery. The selected PCMs are MgCl2.6H2O and KNO3-NaNO3. PCMs are chosen and placed as perthe temperature zones of the receiver. The outdoor test wasconductedto determine the conical receiver's storage performance using cascaded PCMs. The complete melting of PCM attainsat an average receiver surface temperature of 230°C. The complete melting of the PCM in the receiver took around 30 minutes at average radiation around 700 W/m2, and heat stored is approximately 5000 kJ. The estimated number of cavity receivers to be charged on a sunny day is about 10-15 according to the present design and selected PCMs, for later use